2015
DOI: 10.5935/1806-0013.20150050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of body painful areas in patients with muscular temporomandibular disorder: a retrospective study

Abstract: BACKGROUND AND OBJECTIVES:Among temporomandibular disorder classifications, masticatory muscles myofascial pain is the most frequent. Its multifactorial etiology makes its treatment difficult. Identifying other painful sites related to temporomandibular disorders may help controlling comorbidities and, as a consequence, improving their symptoms. This study aimed at evaluating the presence of body pain in temporomandibular disorder patients, the frequency of such reports and their location. METHODS:We have eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…In a similar analysis, Pozzebon et al As said before, the cervical function was impaired in the great majority of the patients with TMD, demonstrating the proximity there is between these two conditions. Such relation is also mentioned by other authors, who stated that most of the patients with TMD presented pain in other parts of the body, of which the cervical region was the most affected; this finding is of great relevance for clinical practice 7,32,33 . Hence, analyzing the results of this likely association in the present research, it was observed that, even though there was no statistical significance (p = 0.178), the cervical disability is aggravated in the proportion that TMD severity is increased; i.e., patients with severe or moderate TMD tend to present greater cervical impairment than patients with mild TMD (Table 2).…”
Section: Discussionsupporting
confidence: 67%
“…In a similar analysis, Pozzebon et al As said before, the cervical function was impaired in the great majority of the patients with TMD, demonstrating the proximity there is between these two conditions. Such relation is also mentioned by other authors, who stated that most of the patients with TMD presented pain in other parts of the body, of which the cervical region was the most affected; this finding is of great relevance for clinical practice 7,32,33 . Hence, analyzing the results of this likely association in the present research, it was observed that, even though there was no statistical significance (p = 0.178), the cervical disability is aggravated in the proportion that TMD severity is increased; i.e., patients with severe or moderate TMD tend to present greater cervical impairment than patients with mild TMD (Table 2).…”
Section: Discussionsupporting
confidence: 67%
“…If the BD-BCI stimulator's maximum available current for the particular channel is lower than the current that meets any of the above conditions, the stimulation was stopped at that current. After each stimulation delivery, the patient was asked to report the perceived intensity, quality, and location of sensation or movement on the patient's body (the anatomical location was identified using a body map which divided the body surface into 45 compartments; Correia et al, 2015 ). The in vivo stimulation pulses delivered to the brain was measured and qualitatively compared between the commercial and BD-BCI stimulators using a commercial handheld oscilloscope (Siglent Technology, Shenzhen, China) connected in parallel to a stimulating electrode pair.…”
Section: Methodsmentioning
confidence: 99%
“…It is also known that individuals with TMJ are 5.5 times more likely to have pain in other joints 2 , and the most reported areas with concomitant pain were the cervical region followed by the low back, shoulders and lower limbs 18,19 . People with TMDs reported more pain during cervical examination in all directions and it was found that the greater the cervical involvement, the greater the degree of temporomandibular involvement 20,21 . Based on these findings, the inclusion of physical examination of the neck during the examination of patients with TMDs is recomended 20 .…”
Section: Contentsmentioning
confidence: 99%
“…People with TMDs reported more pain during cervical examination in all directions and it was found that the greater the cervical involvement, the greater the degree of temporomandibular involvement 20,21 . Based on these findings, the inclusion of physical examination of the neck during the examination of patients with TMDs is recomended 20 . It has been found that the severity of temporomandibular symptoms accompanies the severity of cervical spine disorders, but the reverse does not seem to be true.…”
Section: Contentsmentioning
confidence: 99%